Gessel's concept of free-money eliminating interest through information-money - Omercevic, Edo; Mydin Meera, Ahamed Kameel (2011)
Introduction: Choosing the right monetary system and the kind of money to be used within that system is of immense importance. After all, the concept of Riba that is very much abhorred in Islam, has a lot to do with money and monetary systems. Money and the monetary system lay down the foundation for the exchange, distribution and investment process in the economy and influence the savings and consumption functions as well. Therefore, choosing a wrong money or monetary system might jeopardise the attainment of the Maqasid al-Shari‟ah, i.e. the objectives of Islamic jurisprudence, and thereby bring about negative consequences on Muslim societies. For example, the existence of interest rates or its equivalent in the Muslim world despite its strong prohibition in Islam, the abuse of seigniorage of fiat money, the inequitable distribution of income, inequitable taxation through inflation and many more potential negative impacts of a faulty monetary system could be mentioned. Besides the fact that fiat money has successfully replaced gold and silver as the currency in the Muslim world, a current and most evident problem of the existing monetary establishment is the existence of interest rates in the market. A serious manifestation of this is the merger of the profit rates charged by Islamic financial institutions with interest rates that make them similar to the interest rates themselves. This is what is normally referred to as the convergence between Islamic and conventional banking. Yet, despite being highly condemned, interest rates form an integral part of today‘s global monetary system, including in the Muslim world, regardless of political and ideological differences. Even though there are numerous organisations which are trying to create alternative systems, like the much developed Islamic banking which is growing rapidly, the evolutionary process of the monetary establishment is still stuck with in the current interest-based system. This is despite all the criticism the interest-based system is facing in the literature dedicated to topics related to religion, social economics, development economics, etc. In addition, periodic economic instabilities, called business cycles are accepted as a norm as well, with structural crashes taken as unavoidable part of life.